The Mechanism of Mycobacterium smegmatis PafA Self-Pupylation - Chen, Xuejie (PLoS One, 2016)
PafA, the prokaryotic ubiquitin-like protein (Pup) ligase, catalyzes the Pup modification of bacterial proteins and targets the substrates for proteasomal degradation. It has been reported that that M. smegmatis PafA can be poly-pupylated. In this study, the mechanism of PafA self-pupylation is explored. We found that K320 is the major target residue for the pupylation of PafA. During the self-pupylation of PafA, the attachment of the first Pup to PafA is catalyzed by the other PafA molecule through an intermolecular reaction, while the formation of the polymeric Pup chain is carried out in an intramolecular manner through the internal ligase activity of the already pupylated PafA. Among the three lysine residues, K7, K31 and K61, in M. smegmatis Pup, K7 and K31 are involved in the formation of the poly-Pup chain in PafA poly-pupylation. Poly-pupylation of PafA can be reversibly regulated by depupylase Dop. The polymeric Pup chain formed through K7/K31 linkage is much more sensitive to Dop than the mono-Pup directly attached to PafA. Moreover, self-pupylation of PafA is involved in the regulation of its stability in vivo in a proteasome-dependent manner, suggesting that PafA self-pupylation functions as a mechanism in the auto-regulation of the Pup-proteasome system.